Determinants of the Discount for Lack of Marketability in Business Valuation: Evidence from Indonesia - Catur Budi Nugraha, Tarsisius; Wahyuni, Sri (Journal of Accounting and Finance Management, 2025)
The study intends to identify the determinants of the discount for lack of marketability or DLOM in the Indonesia Stock Exchange. Significant variables are then used to compare high, medium, and low categories of DLOM. The results of this comparison can be used as a basis for calculating this discount in a business valuation in Indonesia. The samples in this study are companies that announced seasoned equity offerings on the market between 2013-2022 through the IDX website, the Reuters database, and the issuer's prospectus. The multiple discriminant analysis shows five significant variables: the percentage of cash to the value of market capitalization, volatility, buyers type, the ratio of EBITDA to the book value of assets, and the ratio of debt to the equity. The result is obtained from the analysis using the restricted stock study. This study uses the theory of asymmetric information and strong-form efficient markets in forming stock prices, to explain the emergence of DLOM.